Time extension factors in construction industry of Pakistan - Gardezi, S.S.S. (Elsevier Ltd, 2014)
The delays in the construction industry are a global phenomenon and are considered as one of the most persistent problems throughout the world. The construction industry of Pakistan is also no exception to it. The key controlling features of time, cost, quality and safety for a project are adversely affected by the impacts of such delays. The delays in construction industry have many after effects among which the main are time extension, cost overrun, disputes, arbitrations and litigations. The main purpose of this study is to identify the delays that result in time extension factors for project completion. Earlier studies have mostly emphasized on the major causes or the effects of project delays. This study investigates the factors contributing in time extensions in construction project according to key participants of the projects i.e. contractors, consultants and the clients. In this regards, the time extension data of almost 50 projects have been consulted to identify the significant factors contributing in time extensions for completion of the projects. From the data, the 27 key factors were identified which have significant contributions in time extensions. Based upon these factors, a questionnaire has was developed and distributed among professional working in the construction industry for their response to assess the contributions of these factors in the time extension grants in construction industry of Pakistan. The study revealed that domestic issues of the country are the major factors resulting in the delayed completion of the projects. Â© 2014 The Authors. Published by Elsevier Ltd.